The development of a novel plant-based biomaterial scaffold for tissue engineering applications - Mamphey, Maame Nicole (Rhodes University, Faculty of Science, Biotechnology Innovation Centre)
Thesis embargoed. Possible release date set for early 2025.
Keywords: Uncatalogued